Experimental investigation on the combustion characteristics of aluminum in air. (December 2016) - Feng, Yunchao; Xia, Zhixun; Huang, Liya; Yan, Xiaoting
Abstract: With the aim of revealing the detailed process of aluminum combustion in air, this paper reports an experimental study on the combustion of aluminum droplets. In this work, the aluminum wires were exposed and heated by a CO2 laser to produce aluminum droplets, and then these droplets were ignited and burnt in air. The changing processes of aluminum wires, droplets and flames were directly recorded by a high-speed camera, which was equipped with a high magnification zoom lens. Meanwhile, the spectrum distribution of the flame was also registered by an optical spectrometer. Besides, burning residuals were collected and analyzed by the methods of Scanning Electron Microscopy (SEM) and Energy Dispersive Spectrometer (EDS). Experimental results show that, during combustion, the aluminum droplet is covered by a spherical vapor-phase flame, and the diameter of this flame is about 1.4 times of the droplet diameter, statistically. In the later stages of combustion, the molten aluminum and condensed oxide products can react to generate gaseous Al and Al2 O spontaneously. Little holes are found on the surface of residuals, which are the transport channels of gaseous products, namely the gaseous Al and Al2 O. The combustion residuals are consisted by lots of aluminum oxide particles with diameters less than 1 μm. Highlights: The diameter of gas-phase flame is about 1.4 times of that of the droplet. The oxide bubbles were observed and the cause of formation of them was analyzed. Several little gas holes were found on the surface of combustion residual.